2013
DOI: 10.2147/dhps.s44525
|View full text |Cite
|
Sign up to set email alerts
|

Risky substance exposure during pregnancy: a pilot study from Lebanese mothers

Abstract: BackgroundThe harmful effects of medication and licit substance use during pregnancy may potentially constitute a major public health concern. Our study aims to assess risky exposure of Lebanese pregnant women to drugs, tobacco, caffeine, and alcohol, and to determine their effect on postnatal outcomes.MethodsWomen at term were addressed after delivery in five university hospitals of Beirut and Mount Lebanon between February and June 2012. A standardized questionnaire was administered to them. Moreover, medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Although it has spread throughout the world, water-pipe smoking is still most pronounced in the eastern Mediterranean region [ 19 ]. We found that 8.2% of pregnant women in our study in southern Iran smoked water-pipe, which is quite similar to the results of studies conducted in Lebanon and Jordan (4-9%) [ 20 , 21 ]. In accordance with previous studies [ 21 , 22 ], most water-pipe smokers in our sample had low SES, more irregular prenatal visits, and more exposure to water-pipe smoke.…”
Section: Discussionsupporting
confidence: 89%
“…Although it has spread throughout the world, water-pipe smoking is still most pronounced in the eastern Mediterranean region [ 19 ]. We found that 8.2% of pregnant women in our study in southern Iran smoked water-pipe, which is quite similar to the results of studies conducted in Lebanon and Jordan (4-9%) [ 20 , 21 ]. In accordance with previous studies [ 21 , 22 ], most water-pipe smokers in our sample had low SES, more irregular prenatal visits, and more exposure to water-pipe smoke.…”
Section: Discussionsupporting
confidence: 89%
“…Other adverse pregnancy outcomes were also assessed in the aforementioned and other studies. The intensity of non-exclusive WPS was inversely correlated with the APGAR scores among newborns at 5 and 10 min in a retrospective study that did not adjust for cigarette smoking, 115 A strong association with the risk of perinatal pulmonary complications (OR=3.65, 95% CI 1.52 to 8.75) was also demonstrated among children born to exclusive WPS mothers. 116 A higher risk of infant mortality among Southern Asian WP smokers was also reported in a cross-sectional study, but the association did not reach statistical significance after adjustment for confounders.…”
Section: Resultsmentioning
confidence: 94%
“…WPS has been associated with obstetric and perinatal complications including low birthweight (LBW). 110–117 infant mortality, 118 low APGAR scores, 115 and pulmonary complications at birth. 116 Studies were primarily retrospective or cross-sectional and were conducted in Lebanon, 110 114–116 Qatar, 111 Iran, 112 113 the Gaza Strip 117 and Cambodia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations